Civil War as Total War : Madison, WI and the Creation of a Homefront - Barth, John (My University, 2011)
This project studied Madison, Wisconsin during the Civil War and analyzes how it served as a ?homefront? during the conflict. It examined how the media, government, soldier interaction, and involvement of women created an atmosphere that led to the mobilization of people in Madison.
Color poster with text and images.
Keywords: Total War--History--Civil War, 1861-1865; United States--History--Civil War, 1861-1865--Participation, Civilian; Madison (Wis.)--History--Civil War, 1861-1865; Posters